Cerebrospinal Fluid Concentrations of Calcitonin Gene Related Peptide in Dogs With Chiari‐Like Malformation - John D. Macri; Courtney Sparks; Zachary Anderson; Natasha Olby (Journal of Veterinary Internal Medicine)
ABSTRACT Background The biomarker Calcitonin Gene‐Related Peptide (CGRP) is elevated in human conditions associated with neuropathic pain, but has not yet been studied in Cavalier King Charles Spaniels (CKCS) with Chiari‐like malformation (CM). Hypothesis/Objectives Cavalier King Charles Spaniels with clinical signs of CMSM would have higher CSF concentrations of CGRP than asymptomatic CKCS. Our aim was to measure CSF CGRP concentrations in CKCS with and without clinical signs of CMSM. Animals Twenty‐nine CKCS drawn from research and clinical cases underwent quantification of pain and scratching, a brain and spinal cord MRI, and lumbar CSF collection. Methods This was a prospective study with both normal and clinically affected CKCS recruited. The CSF concentration of CGRP (C‐CGRP) was measured using an ELISA assay. Dogs were grouped by the presence of SM, pain, and scratching, and concentrations of C‐CGRP were compared between groups using Wilcoxon Rank Sum. The concentration of C‐CGRP, pain score, and SM diameter were evaluated using linear regression. Results Concentration of C‐CGRP was significantly higher in painful dogs (median 116.1, range: 11.6–238.3 pg/mL) as compared to non‐painful dogs (median 77.7 pg/mL, range 0–266.2 pg/mL; p = 0.0124). No significant difference in C‐CGRP concentration was noted between dogs with (median 99.3, range 0–226.6 pg/mL) and without (median 102.2, range 6.0–266.2 pg/mL) SM (p = 0.305). Conclusions and Clinical Importance Cerebrospinal fluid CGRP concentration is elevated in CKCS exhibiting pain regardless of the presence of SM. CGRP might contribute to neuropathic pain in CMSM and could be a target for therapeutic intervention.